Molecular communication from bone to skeletal muscle: an overview - Li, Guobin; Qi, Mingyan; Wang, Yuzhen; Liang, Shibin; Xu, Huiyun (Frontiers in Cell and Developmental Biology, 2025)
The intricate interactions between bone and muscle are central to musculoskeletal health. It was historically assumed that bone and muscle interact through mechanical coupling, that is, skeletal muscles attach to bone and facilitate movement of the bone via muscular contraction. However, recent studies have recognized bone and muscle as endocrine organs, capable of producing and releasing osteokines and extracellular vesicles (EVs) that influence each other’s functions, thereby introducing a novel concept known as “bone-muscle crosstalk”. The influence of muscle on bone has been extensively studied, little has reported regarding the muscle regulation by bone. Emerging studies indicate that the transmission of signaling molecules from bone to muscle is partially mediated by hemichannels and gap junctions formed by connexin 43 (Cx43) in osteoblasts and osteocytes. This review aims to summarize the latest findings on bone-muscle crosstalk, with a particular emphasis on the roles of osteokines and EVs derived from bone. Furthermore, it highlights the channel functions of Cx43 in the release of secretory factors through this crosstalk mechanism. The continued research into bone–muscle crosstalk is expected to identify new therapeutic targets for the twin diseases of osteoporosis and sarcopenia.